Historical Trauma Theory: The Implications for Nursing in Aotearoa New Zealand - McGregor, Jennifer (Auckland University of Technology, 2021)
Historical Trauma Theory conceptualises Indigenous distress in response to colonisation, and is unique in that it focuses on the collective and multigenerational trauma of colonisation from an Indigenous worldview. Historical Trauma Theory links contemporary Indigenous health disparities to the process of colonisation through biological, psychological, and socio-political pathways. Nurses should consider Historical Trauma Theory to understand the implications of colonisation on the wide array of health disparities experienced by Indigenous people. Furthermore, using Historical Trauma Theory as the basis of Indigenous distress provides many possibilities for culturally appropriate healing from historical injustices and the improvement of health outcomes for Indigenous people. The research question for this literature review is: What are the implications of Historical Trauma Theory for nursing practice in Aotearoa New Zealand? This research paper presents the findings of an integrative literature review, which explored the possibility of applying Historical Trauma Theory to nursing practice in Aotearoa. Kaupapa Māori Theory and a decolonising research methodology informed a conceptual and empirical review of the Historical Trauma Theory within comparative Indigenous communities, health care practice, and nursing literature. An integrative literature review method enabled a variety of literature to be included, and it is argued to be an appropriate method for research within the nursing field. This research focussed on the application of Historical Trauma Theory to health care practice, specifically the implications for generic nursing practice (both indigenous and non-indigenous nurses) in a Māori context in Aotearoa. Few articles conceptualise Historical Trauma Theory within the context of Aotearoa and this dissertation is the first attempt to do so from a nursing perspective. The literature available within an Aotearoa context does, however, resonate with international concepts and debates, such as the need for culturally grounded interpretations of historical trauma. Five main themes emerged from the literature: 1) the interpretation of Historical Trauma Theory, 2) the multigenerational transmission of historical trauma, 3) linking ‘historical’ events to contemporary Indigenous health, 3) healing from historical trauma, and 5) Historical Trauma Theory and health care practice. The findings have been used to construct a discussion chapter on the implications for nursing within Aotearoa. Given the lack of Historical Trauma Theory conceptualisation within Aotearoa and the profession of nursing, the discussion chapter focuses on how Historical Trauma Theory can support an existing nursing model, Wilson and Barton’s (2008) Te Kapunga Putohe, to guide all nurses when practising within a Māori context. The discussion also highlights new avenues for how Historical Trauma Theory could contribute to generic nursing practice and theory in Aotearoa. The implications for nursing theory and practice when caring for Māori include understanding the ongoing effects of colonisation on various social and health outcomes, the importance of culturally grounded health care practice including nursing practice, whānaungatanga, cultural connectedness, and tino rangatiratanga. To summarise, nursing praxis needs to incorporate Historical Trauma Theory as a framework for understanding the underlying cause of the major health disparities still endured by Māori nearly two centuries since the colonisation of Aotearoa began.
Keywords: Historical Trauma Theory; Nursing; Māori; Indigenous